Exploring the nexus of migration dynamics and urban expansion: key drivers of horizontal spatial growth in Woldia Township, Ethiopia - Fente, Mulu Fasigo; Abebe, Birhanu Girma; Woldeamanuel, Mintesnot Gebeyehu (Frontiers in Human Dynamics, 2025)
Ethiopia remains one of the least urbanized countries globally, although many of its urban centers, including Woldia, the capital of the North Wollo Zone, are undergoing rapid growth. Woldia has recently faced significant urban challenges due to its expanding horizontal growth. One of the major issues associated with this growth is the increasing demand for land and space, driven by population pressure, largely attributed to migration. This migration has led to the annexation of agricultural land at the rural periphery, further contributing to the town’s horizontal expansion. This study aims to explore the key drivers behind the horizontal growth of Woldia, particularly in its peripheral areas. Data were collected through a structured questionnaire administered to a randomly selected sample of 395 respondents, complemented by key informant interviews and secondary data sources. Both qualitative and quantitative analytical methods were employed. The findings indicate that poor social services and poverty in migrants’ areas of origin are the primary push factors. Conversely, improved social infrastructure and job opportunities at the destination are the main pull factors. Consequently, the influx of migrants has resulted in significant pressure on peri-urban areas, where housing availability and accessibility remain limited. The study recommends that local government officials and urban planners enhance their understanding of migration dynamics to effectively manage the town’s spatial expansion and address the challenges of accommodating a growing population.